2004
DOI: 10.1093/ije/dyh251
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of genotypes in multiple chemical sensitivity: CYP2D6, NAT1, NAT2, PON1, PON2 and MTHFR

Abstract: A genetic predisposition for MCS may involve altered biotransformation of environmental chemicals. The CYP2D6 enzyme activates and inactivates toxins; the NAT2 enzyme bioactivates arylamines to protein-binding metabolites. A gene-gene interaction between CYP2D6 and NAT2 suggested that rapid metabolism for both enzymes may confer substantially elevated risk (OR = 18.7, P = 0.002). Our finding parallels others' observation of a link between PON1 heterozygosity and neurological symptoms in Gulf War syndrome. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 36 publications
7
64
1
1
Order By: Relevance
“…Previous studies suggested that the polymorphic site in PON1 was related to an increased risk of MCS [23] and Gulf War Syndrome, which is an MCSrelated syndrome [15]. However, no significant association between the Gln192Arg polymorphism and PON1 was obtained in our study.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous studies suggested that the polymorphic site in PON1 was related to an increased risk of MCS [23] and Gulf War Syndrome, which is an MCSrelated syndrome [15]. However, no significant association between the Gln192Arg polymorphism and PON1 was obtained in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…Several reports suggest that MCS patients who are aware of their chemical intolerance avoid exogenous chemicals such as those from smoking [23,24]. Tobacco smoke contains many kinds of chemicals, including formaldehyde and acetaldehyde [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the study of genetic polymorphisms, particularly regarding the enzymes involved in the metabolism of drugs and substances commonly used in the perioperative period, it was possible to obtain the definition of the genotype associated with each enzyme and to perform, than, a prediction and estimate of the impact on the metabolism of each classes of drugs (8). In the study were also included some transporter proteins for drugs within the liver microsomes (ABCC1 and 2) and enzymes responsible for the control of intracellular oxidative stress, indirect indicator of metabolic overload.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies underway to determine the aetiological source of IEI. Genetic polymorphisms in drug-metabolising enzymes have previously been examined; 12,13 however, genetic involvement in IEI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental exposures to various chemicals, [12][13][14][15] as well as studies of groups at high risk for chemical exposures, 16 have also failed to identify any differences between IEI patients and control subjects. Thus, the hypothesis that frequent chemical exposure causes an increased risk for developing IEI has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%